The effectiveness of KONI pre-arbitration in the settlement of National Sports Disputes - Mohamad Alim Rifay Thalib; Fence M. Wantu; Dolot Alhasni Bakung (Yayasan Cerdas Pedia Indonesia, 2026)
This study analyzes the effectiveness of KONI pre-arbitration in resolving national sports disputes and protecting athletes’ rights. The issue is significant because sports disputes require mechanisms that are faster, more adaptive, and more compatible with sports governance than ordinary litigation. This normative legal research uses statutory and historical approaches, supported by legal interpretation of primary regulations, organizational documents, and relevant scholarly literature. The findings show that KONI pre-arbitration has three strategic functions: facilitating internal deliberation, filtering disputes before formal arbitration, and serving as a procedural gateway to the Indonesian Sports Arbitration Board. Its effectiveness depends on clear operating standards, formal documentation, administrative support, institutional compliance, and consistent protection of athletes affected by organizational or contractual disputes. Strengthening standard procedures, minutes of settlement or deadlock, referral mechanisms, and administrative enforcement is therefore necessary to ensure legal certainty, prevent prolonged conflict, and safeguard athletes’ professional interests effectively within the national sports system.